2016
DOI: 10.1007/s00330-016-4307-5
|View full text |Cite
|
Sign up to set email alerts
|

Submillisievert CT using model-based iterative reconstruction with lung-specific setting: An initial phantom study

Abstract: • Lung-specific submillisievert 10 mA-MBIR CT setting has similar performance to 50 mA-FBP • The new lung-specific settings improve vessel clarity and blurring of borders • The new settings may provide more appropriate images than conventional settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Any reduction in the radiation dose decreases image quality and increases noise. However, this increase can be overcome using IR algorithms [6, 12, 27, 35]. In fact, although the IR-HP-CT tube current was only 30 mAs, IR-HP-CT images were less noisy than LDCT images using a tube current of 40 mAs.…”
Section: Discussionmentioning
confidence: 99%
“…Any reduction in the radiation dose decreases image quality and increases noise. However, this increase can be overcome using IR algorithms [6, 12, 27, 35]. In fact, although the IR-HP-CT tube current was only 30 mAs, IR-HP-CT images were less noisy than LDCT images using a tube current of 40 mAs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MBIR often is considered as a time-consuming algorithm. [ 23 ] In another study, Afadzi et al . assessed the low-dose technique at three dose levels of CTDI vol = 0.25, 0.49, 0.74 mGy, with the adaptive statistical iterative reconstruction (ASIR-V) algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Veo 3.0 had some setting options for reconstruction: Stnd setting was a conventional setting that had the same physical characteristics as Veo 2.0 (previous generation of MBIR and previous version of Veo 3.0); and RP20 setting was one of the lung settings prepared to provide high-resolution images. [14] Ultra-low-dose CT was reconstructed using FBP with sharp kernel (uFBP), MBIR with the RP20 setting (uMBIR-Lung), and MBIR with the Stnd setting (uMBIR-Stnd). Standard-dose CT was reconstructed using FBP with sharp kernel (sFBP) at the same section thickness, matrix size, and field of view.…”
Section: Methodsmentioning
confidence: 99%
“…[12] Although the previous generation of MBIR had no option for specific body regions, the latest generation of MBIR has some clinical settings for the head, lung, and abdomen. [13,14] Several studies reported that the latest-generation MBIR with the lung setting could provide higher resolution images and more appropriate image quality for lung assessment than the conventional setting that has the same physical characteristics as previous generation of MBIR. [13,14]…”
Section: Introductionmentioning
confidence: 99%